O papel do empresário artístico na gestão de carreiras musicais após a transformação da indústria da música - Carvalho, Anita Vasconcelos de (2019)
Brazil is the second largest live music market in Latin America, second only to Mexico, according to PwC (2016) Entertainment and Media Outlook. Revenue from this segment in 2010 was $ 165 million. In 2014, it increased to $ 205 million and is expected to reach $ 280 million in 2019. Despite the significant numbers, there is no structural formalization of this activity in Brazil, especially regarding the strategic management of artistic careers. This paper aims to study the role of the artist manager in the development of artistic careers in the music sector in the context of digital communication and information technologies, which significantly altered the relationships between the players in the music industry. It was found that the transformation of the music market has expanded the responsibilities of this professional, who according to the various market professionals interviewed, is a key agent in the music production chain. The research was conducted in two stages. In the quantitative phase, separate online forms were sent electronically to artists' representatives and to the artists themselves, obtaining 100 answers for each. In the qualitative stage, ten music market agents were interviewed, including record and radio executives, concert hall managers, artists and artists’ managers. With the research conducted it was possible to estimate the live show market in Brazil, identifying revenues, number of shows and average price practiced, constituting an important contribution to this market, lacking the production of scientific data. The work contributes to improve the management of artistic careers by artist managers, as, among other things, it proposes a systematization of the business models practiced in this market